PERAN INTERNAL DAN EKSTERNAL AUDIT SEBAGAI BAGIAN dari PENERAPAN GOOD CORPORATE GOVERNANCE (Studi Kasus: PT. Bank Mandiri, Tbk) - Theresia Hesti Bwarleling (Universitas Bunda Mulia, 2017)
With the implementation of GCG, it is expected to maintain the control of the company that can reduce the possibility of mismanagement and create added value for the stakeholders of optimal business. Through the help of internal and external auditors, the company is expected can provide the assurance to stakeholders that management is acting in the best way, so that business processes implemented in accordance with the concept of Good Corporate Governance to achieve growth and profitability in the long run and win the global business competition.Key words : Good Corporate Governance, internal and external auditors